Chemical Variation of Chenpi (Citrus Peels) and Corresponding Correlated Bioactive Compounds by LC-MS Metabolomics and Multibioassay Analysis - Yang, Mei; Jiang, Zongde; Wen, Mingchun; Wu, Zhenfeng; Zha, Minyu; Xu, Wen; Zhang, Liang (Frontiers in Nutrition, 2022)
The peel of Citrus reticulata ‘Chachi’ (CP) possesses various health-promoting benefits, and is not only one of the most famous Chinese herbal medicine but also an ingredient in fermented foods. In the present study, the effects of storage years (1, 3, 4, 5, 6 and 11 years) on the chemical profiling and potential bioactive compounds of CP were compared by metabolomics and in vitro bioactivity analysis. With the increase of storage time, the content of hesperidin significantly decreased, but nobiletin, 3,5,6,7,8,3',4'-heptamethoxyflavone and tangeretin was increased. Meanwhile, the antioxidant activity of CP was enhanced. Phenolic acids, flavonol glycosides, fatty acids and alkyl glycosides were marker compounds which were responsible for distinguishing the storage time of CP. Correlation analysis suggested some polyphenols including quercetin-glucoside, quinic acid, trihydroxydimethoxyflavone, and rutin were potential antioxidant compounds in CP. The dichloromethane and n-butanol fractions showed the better antioxidant capacity and inhibitory effects on glucose-hydrolysis enzymes. They mainly contained ferulic acid, nobiletin, 3,5,6,7,8,3',4'-heptamethoxyflavone, kaempferol and hesperidin.